2018
DOI: 10.1007/s13197-018-3301-0
|View full text |Cite
|
Sign up to set email alerts
|

Edible coating with probiotic as a quality factor for minimally processed carrots

Abstract: The objectives of this study were to elaborate an edible coating based on sodium alginate with probiotic potential and to evaluate the coating's performance with respect to microbial viability and the characteristics of safety and freshness of minimally processed carrots stored at 8 ± 2 °C. Carrot slices were submerged in a sodium alginate solution with and without the addition of La-14 (7.36 log CFU/g), and gelling was activated by subsequent immersion in a calcium chloride solution. Physical, chemical and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…It shows that the water vapor resistance of MPC was improved by the coating process. Similar results have been observed previously for lightly processed carrots treated with cellulose‐based (Li & Barth, 1998) and sodium alginate‐based coatings (Shigematsu et al., 2018). It is worth to mention that the coating was effective in controlling the mass transfer across the carrot surface, despite the lack of a homogenous distribution of the wax phase (Figure 3).…”
Section: Resultssupporting
confidence: 90%
“…It shows that the water vapor resistance of MPC was improved by the coating process. Similar results have been observed previously for lightly processed carrots treated with cellulose‐based (Li & Barth, 1998) and sodium alginate‐based coatings (Shigematsu et al., 2018). It is worth to mention that the coating was effective in controlling the mass transfer across the carrot surface, despite the lack of a homogenous distribution of the wax phase (Figure 3).…”
Section: Resultssupporting
confidence: 90%
“…in, 2018. Similarly, reduction in the pH of carrot juice was observed due to the addition of Lactobacillus acidophilus by Shigematsu et al., 2018.…”
Section: Resultsmentioning
confidence: 76%
“…Reduction in the pH due to the inoculation of B. animalis ssp.lactis in yogurt was suggested bySenadeera et al in, 2018. Similarly, reduction in the pH of carrot juice was observed due to the addition of Lactobacillus acidophilus byShigematsu et al, 2018.…”
mentioning
confidence: 90%
“…Similarly, Shigematsu et al. (2018) revealed that the incorporation of Lactobacillus acidophilus La‐14 in sodium alginate‐based edible coating effectively prevented the growth of molds and yeasts in treated carrot slices. The major function of LABs in foods preservation is mostly due to their inhibitory effects against pathogens.…”
Section: Resultsmentioning
confidence: 95%
“…Shigematsu et al. (2018) also found that when L. acidophilus was incorporated into alginate‐based coatings, the color of carrot slices was markedly preserved. It is known that coatings are efficient moisture and physical barriers that can postpone the dehydration (Almenar et al., 2007).…”
Section: Resultsmentioning
confidence: 98%